Solar-Powered IoT-Based Home Fire Early Warning and Protection System - Muhammad Arief Wicaksono; Amirullah Amirullah; Boonyang Plangklang (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
This paper presents the implementation of a prototype of a fire early warning system in a residential house using temperature and smoke sensors supplied by an Internet of Things (IoT) based solar module. The 10 Wp solar module is the energy source connected to a 12V battery via a solar charge controller (SSC). Data retrieval is carried out through testing by the MQ-2 Sensor and LM35 Sensor, respectively, to detect smoke (gas) and heat. The system then activates the buzzer, sends data from the detection of the status and level of smoke (gas) and heat to the smartphone screen and liquid crystal displays (LCD) in the form of an alarm, and orders the PLN switch to work to cut off the electricity. The results of the tool test show that the proposed prototype is able to provide early warning notifications regarding the status and level of smoke (gas) and heat - both from the LCD and remotely from the smartphone, and is able to activate the relay dan order the switch cuts off the electricity to prevent fire. The prototype system's source is supplied by solar modules independently, making it applicable in remote areas with limited electricity access-compared to the previous model which was supplied solely by the electricity grid.